How an Economic Imperative is Constructed: The Case of Oil Exploitation in Uganda - Wokuri, Pierre (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2023)
A great deal of research has documented how extractive resources are governed once their exploitation has begun, how transnational actors and factors play a role in extractive industries, and how states stick to a path of dependency towards fossil fuel exploitation. However, most of this previous research has not taken sufficiently seriously domestic politics. Furthermore, there has been little work on how dependency is constructed before exploiting these resources. This article fills that gap by showing how oil exploitation has been constructed as an economic imperative in Uganda. Building on a research design with a broad range of empirical fingerprints, this article shows that construction of oil as an economic imperative in Uganda is based on two processes: 1) embedding the meso level within the macro level through a long-term horizon; and 2) rendering the contingent necessary through a combination of material and immaterial strategies of state political control.